Can Survey Evidence Shed Light on Spillovers from Foreign Direct Investment? - Javorcik, Beata S. (World Bank, 2012)
Although some economists remain skeptical of the existence of positive externalities associated with foreign direct investment (FDI), many countries spend large sums attracting foreign investors in the hope of benefiting from knowledge spillovers. Data collected through enterprise surveys conducted in the Czech Republic and Latvia suggest that the entry of multinationals affects domestic enterprises in the same industry or in upstream or downstream sectors through multiple channels. Some of these channels represent true knowledge spillovers while others have positive or negative effects on domestic producers in other ways. The relative magnitudes of these channels depend on host country conditions and the type of FDI inflows, which explains the seemingly inconsistent findings of the literature. The focus of the debate should shift from attempting to generalize about whether or not FDI leads to productivity spillovers to determining under what conditions it can do so.